Accuracy of intraocular lens power calculation in pediatric cataracts with less than a 20 mm axial length of the eye - Joshi, Purushottam; Mehta, Raman; Ganesh, Suma (Nepalese Journal of Ophthalmology, 2014)
Introduction: Selection of an appropriately-powered IOL is a complex issue, especially in eyes with an axial length of less than 20 mm in pediatric cataract. Objective: To assess the accuracy of IOL power calculation formulae in pediatric cataracts in eyes with an axial length of less than 20 mm. Materials and methods: The records of children less than 15 years old with congenital cataract who had undergone primary IOL implantation were analyzed. Main outcome measures: The variables studied were axial length, keratometric values and the prediction error. The data were analyzed for prediction error determination using the SRK II, SRK T, Holladay 1 and Hoffer Q IOL power calculation formulae. The formula that gave the best prediction error was identified. Results: Twenty-eight eyes of 19 children were included in the study. The absolute prediction error was found to be 1.84 ± 2.09 diopters (D) with SRK II, 2.93±3.55D with SRK T, 3.63±4.06D with Holladay 1, and 4.83±5.02D with Hoffer Q. The number of eyes with the absolute prediction error within 0.5 D was 6 (21.42%) with SRK II, 4 (14.28%) with SRK T, 1 (3.57%) with Holladay 1, and 3 (10.71%) with Hoffer Q. The absolute prediction error with SRK II formula was significantly better than that with other formulae (P < .001). The axial length influenced the absolute prediction error with Hoffer Q formula (P = 0.04). The mean keratometry influenced the prediction error with SRK T formula (P = 0.02), Holladay 1 formula (P = 0.02) and Hoffer Q formula (P = 0.02). Conclusion: Although the absolute prediction error tends to remain high with all the present IOL power calculation formulae, SRK II was the most predictable formula in this study. DOI: http://dx.doi.org/10.3126/nepjoph.v6i1.10773 Nepal J Ophthalmol 2014; 6 (2): 56-64